Effect of Hot Isostatic Pressing Treatment on Refractory High-Entropy Alloy WTaMoNbV Produced by Laser Powder Bed Fusion Process - Tomer Ron; Avi Leon; Maxim Bassis; Zhan Chen; Amnon Shirizly; Eli Aghion (Metals)
The present study aims to assess the impact of hot isostatic pressing (HIP) treatment on refractory high-entropy alloy (HEA) WTaMoNbV produced by the laser powder bed fusion (LPBF) process. This was carried out by examining the functional properties of this HEA in terms of mechanical and environmental performance. The microstructure of the tested HEA was evaluated using optical microscopy, scanning electron microscopy (SEM), and X-ray diffraction (XRD). Mechanical properties were examined via compression tests, while environmental behavior was evaluated by immersion tests and potentiodynamic polarization. The obtained results demonstrate that HIP treatment improved the alloy’s density from 11.27 to 11.38 g/cm3 and increased its ultimate compression strength by 11.5% (from 1094 to 1220 MPa). This modest favorable effect was attributed to the improvement in bulk properties by eliminating a large part of the sub-grain boundaries and reducing the amount of inherent printing defects, mainly in the form of internal cracking. The advantages offered by HIP were also manifested in surface quality improvement from N11 to N10 grades and enhanced environmental performance, reducing pitting density from 34,155 to 9677 pits/cm2.